Management and quality of life extranodal non hodgkin lymphoma of testis - Bagus Aulia Mahdi; Pradana Zaky Romadhon; Ugroseno Yudho Bintoro; Merlyna Savitri; Putu Niken Ayu Amrita; Muhammad Noor Diansyah; Ami Ashriati Prayoga; Kartika Prahasanti (Universitas Muhammadiyah Surabaya, 2022)
Extranodal non-Hodgkin lymphoma still seems to be a rare case and an issue to discuss a lot. Clinical evidence and guidelines on treatment have not yet been widely published and accessible. We present a case of a forty-five-year-old male with the chief complaint of a bulky and huge right mass in the testis with an ulcer on it. The patient underwent an orchiectomy, and the biopsy showed a malignant round cell tumor, suspected as non-Hodgkin lymphoma. The patient then received the following treatment: chemotherapy with R-CHOP regiment every three weeks, consisting of 6 cycles showing shrinkage size of the testis by day 7 and final complete response after 4th cycle with ADE grade 0 no sexual activity disorder after chemotherapy. This raises hope in developing treatment modalities that the right choice on chemotherapy regimen with complete control on the drug effects may improve clinical outcome and patient’s quality of life.